Incomplete urban projects: urban voids in post-high speed train Zaragoza - Carmen Bellet Sanfeliu; María Pilar Alonso Logroño (Boletín de la Asociación de Geógrafos Españoles)
The arrival of the high-speed train coincided with a boom in the property market and expectations of economic growth throughout the country. The new infrastructure was accompanied by a plethora of urban projects and real estate developments. This was the case in Zaragoza, where the arrival of the new train service became a major instrument of urban development. However, many of these projected changes were dependent on development rights and the sale of former railway land, but the advent of the crisis paralysed these developments, leaving a desolate urban landscape.